Intrauterine Extremity Gangrene and Cerebral Infarction at Term: A Case Report - M. Tanvig; J. S. Jørgensen; M. Nybo; G. Zachariassen (Case Reports in Pediatrics)
Intrauterine extremity gangrene in combination with cerebral infarction is a serious and rare event. We present a case with a healthy mother who gave birth to a child with this condition. At term, the mother presented at the antenatal clinic with decreased fetal movements. Cardiotocography (CTG) showed signs of fetal distress and a caesarean section was performed. The left arm of the newborn was found gangrenous. Amputation of the arm was necessary and the child was subsequently treated with anticoagulant therapy due to thrombosis and cerebral infarction in the left hemisphere found by magnetic resonance imaging (MRI). At one year of age the boy was doing well and had prosthesis as a left arm. He had no signs of further complications. Despite thorough examination of the parents and the child, the reason for the thrombosis is still unknown.